Accuracy of ultrasonography in predicting vesicoureteral reflux in children: A meta-analysis. (3rd July 2016) - Saltychev, Mikhail; Ristola, Marko Tapani; Laimi, Katri; Hurme, Timo
Abstract: Objective: The aim of this study was to assess the existing evidence on the accuracy of renal and bladder ultrasonography in predicting vesicoureteral reflux in children with first urinary tract infection. Materials and methods: The CENTRAL, MEDLINE, Embase and Web of Science data sources were searched. A random effects meta-analysis was conducted. Results: Fourteen studies, involving 3544 participants, fulfilled the inclusion criteria. The risk of bias and concern regarding applicability were considered high in four studies. The pooled sensitivity was 0.37 [95% confidence interval (CI) 0.34 to 0.40], specificity 0.81 (95% CI 0.80 to 0.83), positive likelihood ratio 2.0 (95% CI 1.61 to 2.50), negative likelihood ratio 0.75 (95% CI 0.65 to 0.86), diagnostic odds ratio 3.03 (95% CI 2.10 to 4.37) and area under the curve 0.72. Conclusion: There is no evidence that renal and bladder ultrasonography should be recommended as a test to predict a vesicoureteral reflux in children with their first urinary tract infection.